Peningkatan Kesadaran Masyarakat Untuk Membayar Pajak : Studi Pada Program Kerja KKN Mahasiswa FH UNIMAS Mojokerto di Desa Mojodowo Kecamatan Kemlagi - Derta Nur Anita; Dedy Muharman; Mochammad Yhoga Suwito Putra; Mega Putri Ningsih; Renaldi Dwi Setiawan; Rizka Ananda; Rendi Firdaus Amrul Rozak; Moch Siham Abanberda; Aldo Putra Pratama; Seno Bayu Aji; Syahari Awang; Dimas Bagus Pierera; Aan Nur Alvian; Nurul Lila Buantiwati Ningsih; Irwan Siswanto (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Discussing taxation, taxes have a very urgent position in the discussion of state life. Because taxes are funds that are really needed to finance most of the expenditure for the development of the country so that it is hoped that it will bring prosperity to society. This research was conducted to find out about the form of the tax socialization program held by KKN students and how the community responded to the existence of the tax socialization program using qualitative research methods. The results of this research show that the socialization program was held by UNMAS Mojokerto KKN students